Reseñas (1985)
JURASSIC-CETACEOUS BIOCHRONOLOGY and amp; BIOGEOGRAPHY OF NORTH AMERICA. Ed. by G. E. G. Westermann.- Geol. Assoc. Canada, Spec. Paper 27 315 pp. 1984. / The Andes: A Geological Review. By Werner Zeil.- Beiträge zur regionalen Geologie der Erde, Bd. 13, 260 pp., 150 Illustr., Gebrüder Brntraeger, Stuttgart, 1979. / ALMEIDA, F. F. M. de and amp; HASUI, Y. (1985): The Central Brazil Shield Reviewed.- Episodes, Vol. 8, No.1, pp, No. I, pp. 29-37, IUGS, Ottawa. / GEOLOGIE ET PALEOECOLOGIE DES RECIFS, (Edit. J. Geister and amp; R. Herb) 3éme Cycle en Sciences de la Terre, Institut de Géologie de I'Université de Berne, Suiza, 1984. / GEISTER, J. (1984): Recifs Pleistocenes de la mer des Caraibes: Aspects Geologiques et Paléoecologiques.- In Géologie et Paléoecologia des Recifs (Edit. J. Geister R. Herb). 3eme Cycle en Sciences de la Terre, Institut de Geologie de l'Universite de Berne, 34 p. 21 Figs. / GEODYNAMICS OF THE EASTERN PACIFIC REGION, CARIBBEAN AND SCOTIA ARCS.- R. Cabré, S. J., Edit. Geodynamics Ser., Vol. 9, pp. 1-170, American Geophysical Union-Geological Society of America, 1983. / RAMIREZ, J.E., DUQUE, CARO, H., GOBERNA, J.E. TOUSSAINT, J.F. (1983): Geodynamic Research in Colombia (1972-1979).- In Geodynamics of the Eastern Pacific Region, Caribean and Scotia Arcs (Edit. R. Cabre, S.J.), Geodyn. Ser., 9:41-62,4 Figs. / GEOLOGIA NORANDINA (Publicación de la Sociedad· Colombiana de Geología), No.8, 69 pp., Diciembre de 1983. Apartado Aéreo 4865, Bogotá, Colombia.